Characterisation of patients with supine nighttime reflux: observations made with prolonged wireless oesophageal pH monitoring. Issue 2 (11th June 2021) - Oude Nijhuis, Renske A. B.; Sweis, Rami; Abdul‐Razakq, Humayra; Schuitenmaker, Jeroen M.; Wong, Terry; Rusu, Radu‐Ionut; Oors, Jac.; Smout, Andreas J. P. M.; Bredenoord, Albert J.
Summary: Background: Although nighttime reflux symptoms are common, the presence of nocturnal reflux is seldom confirmed with a standard 24 hours pH study. Aim: To study patients with supine nighttime reflux symptoms using prolonged wireless pH monitoring. Methods: In this retrospective study, patients with typical acid reflux symptoms were studied using 96‐h pH monitoring. Patients with nighttime reflux symptoms were compared to those without. Night‐to‐night variability and diagnostic accuracy of 24‐, 48‐ and 72‐hours pH studies compared to the 96‐hours "gold standard" were evaluated. Results: Of the 105 included patients (61.9% females; mean age 46.8 ± 14.4 years), 86 (81.9%) reported nighttime reflux symptoms, of which 67.4% had pathological supine nocturnal acid exposure in at least one night. There was high variance in night‐to‐night acid exposure (94% [IQR0‐144]), which was larger than the variance in upright acid exposure (58% [IQR32‐88]; P  < 0.001). When analysing the first 24 hours of the pH study, 32% of patients were diagnosed with pathological supine nighttime acid exposure versus 51% of patients based upon the 96‐hours pH‐test. The diagnostic accuracy and yield improved with study duration ( P  < 0.001). Reflux episodes with a lower nadir pH or longer acid clearance time were more prone to provoke nightly symptoms. Conclusions: The majority of patients with nocturnal reflux symptoms had pathological acid exposure in at least one night of the prolonged pH recording. A high night‐to‐night variability in acid exposure reduces the clinical value and diagnostic yield of pH monitoring limited to 24 hours. Prolonged testing is a more appropriate diagnostic tool for patients with nocturnal reflux symptoms. Abstract : Prolonged pH monitoring provided objective evidence of reflux at night in the majority of patients who complain of nighttime reflux symptoms. High night‐to‐night variability reduces the clinical value of pH monitoring limited to 24h. Prolonged testing improved the diagnostic yield and accuracy for nocturnal reflux diagnosis.